2016
DOI: 10.1371/journal.pone.0156115
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Melanoma with Brain Metastasis: Report of 193 Patients with New Observations

Abstract: BackgroundBrain metastasis is a common endpoint in patients suffering from malignant melanoma. However, little is known about factors that predispose to brain metastases.ObjectiveWe performed a retrospective clinical and pathological investigation of melanoma patients with brain metastases in order to better characterise this patient population.Methods193 melanoma patients with brain metastasis histologically diagnosed between 1990 and 2015 at the University Hospital Zurich were retrospectively identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…Although other studies [8,25] found that NM histologic type was associated with BM development, we did not see this when corrected for tumor depth. Our patients with BM were predominantly male, as seen in other studies [8,12,17,26], although our stage-matched control group was similarly male-predominant. A review of multiple studies concluded that male patients with BM have a poorer prognosis [18], although we did not address that issue here.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Although other studies [8,25] found that NM histologic type was associated with BM development, we did not see this when corrected for tumor depth. Our patients with BM were predominantly male, as seen in other studies [8,12,17,26], although our stage-matched control group was similarly male-predominant. A review of multiple studies concluded that male patients with BM have a poorer prognosis [18], although we did not address that issue here.…”
Section: Discussionsupporting
confidence: 69%
“…Prior retrospective studies of melanoma patients with BM examined cohorts ranging in size from 49 to 670 patients [5,6,8-12]. The rate of BM in these cohorts was approximately 10% [5,6,8,9,11,13], which corresponds to the expected risk of developing BM after a diagnosis of primary cutaneous melanoma [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cases of fully regressive melanomas are described in the literature. Regarding the metastatic sites, brain is the commonest with an incidence of 91% in cutaneous melanoma due to the capacity of tumoral cells to migrate along the external surfaces of vascular channels without extravasation (11). The majority of regressive melanomas were described after the occurrence of metastases, being one of the reasons that regression is considered to be a negative prognostic factor in melanoma (12).…”
Section: Discussionmentioning
confidence: 99%
“…Complications of brain lesions (e.g., bleeding, stroke, epilepsy) are the direct cause of death in most of these cases. On the other hand, prognosis of melanoma patients with brain metastases is poor, with median survival ranging from 4 to 10 months in different studies [1, 2]. Significant therapeutic advances have been seen in the field of MM in recent years.…”
Section: Introductionmentioning
confidence: 99%